Implementasi Konseling Suryomentaram bagi Guru BK SMA/SMK di Kota Malang - Atmoko, Adi; Utami, Nugraheni Warih; Probowati, Devy; Multisari, Widya (Institute for Research and Community Service (LP2M), Universitas Negeri Malang, 2023)
Prokastinasi akademik yang terjadi di kalangan siswa SMA mengalami peningkatan seiring berlalunya pandemic Covid-19 dan meningkatnya perkembangan teknologi dan media sosial. Siswa lebih memilih menunda mengerjakan tugas dan mengalami kejenuhan dalam kegiatan belajar. Prokastinasi akademik menjadi masalah yang harus segera ditangani di sekolah, karena berdampak pada prestasi akademik siswa. Tujuan kegiatan pengabdian yaitu untuk meningkatkan kompetensi guru Bimbingan Konseling (BK) dalam melaksanakan konseling dengan pendekatan Suryomentaram, sehingga dapat meningkatkan kualitas pelaksanaan konseling yang dilakukan Guru BK dalam membantu menyelesaikan masalah prokastinasi akademik siswa. Metode belajar melalui tindakan (learning by doing) menjadi alternatif yang akan membantu guru BK dalam mengembangkan keterampilan konseling dengan pendekatan Suryomentaram melalui penyampaian informasi dan implementasi konseling pada siswa yang mengalami prokastinasi akademik. Hasil pelaksanaan pengabdian adalah peningkatan pengetahuan guru BK dan peningkatan keterampilan guru BK di SMA dan SMK dalam melaksanakan proses konseling dengan menggunakan pandangan Suryomentaram dalam mengatasi prokastinasi akademik siswa. Kata kunci—Konseling Suryomentaram, Guru Bimbingan Konseling, Pendampingan Guru Abstract Academic procrastination that occurs among high school students has increased along with the passing of the Covid-19 pandemic and the increasing development of technology and social media. Students prefer to postpone doing assignments and experience boredom in learning activities. Academic procastination is a problem that must be addressed immediately in schools, because it has an impact on students’ academic achievement. The aim of the service activity is to increase the competency of Counseling Guidance (BK) teachers in carrying out counseling using the Suryomentaram approach, so that they can improve the quality of counseling carried out by BK teachers in helping to solve students’ academic procrastination problems. The learning by doing method is an alternative that will help guidance and counseling teachers in developing counseling skills using the Suryomentaram approach through conveying information and implementing counseling for students who experience academic procrastination. The results of the implementation of the service are an increase in the knowledge of guidance and counseling teachers and an increase in the skills of guidance and counseling teachers in high schools and vocational schools in carrying out the counseling process using Suryomentaram’s views in overcoming students' academic procrastination. Keywords—Suryomentaram Counseling, Teacher Guidance Counseling, Teacher Mentoring